Socioeconomic inequalities in maternal healthcare utilization: An analysis of the interaction between wealth status and education, a population-based surveys in Tanzania. - Deogratius Bintabara; Ipyana Mwampagatwa (Public Library of Science (PLoS), 2023)
Limited scientific, evidence has so far described the interactions between socioeconomic factors and the gap of inequalities in maternal healthcare utilization. This study assessed the interaction between wealth status and education to identify women with greater disadvantage. This analysis used secondary data from the three most recent rounds (2004, 2010, and 2016) of the Tanzania Demographic Health Survey (TDHS). Maternal healthcare utilization was assessed based on six services (outcomes) which are i) booking during the first trimester (bANC), ii) at least four antenatal visits (ANC4+), iii) adequate antenatal care (aANC), iv) facility-based delivery (FBD), v) skilled birth attendance (SBA), vi) cesarean section delivery (CSD). The concentration curve and the concentration index were used to measure socioeconomic inequality in maternal healthcare utilization outcomes. The interaction coefficients suggest that each unit increase in the wealth status is significantly associated with higher odds of utilizing all maternal healthcare services for women with primary and secondary or higher education compared to those with no education (booking during the first trimester [AOR = 1.30; 95% CI: 1.08-1.57], at least four antenatal visits [AOR = 1.16; 95% CI: 1.01-1.33], facility-based delivery [AOR = 1.29; 95% CI: 1.12-1.48], skilled birth attendance [AOR = 1.31; 95% CI: 1.15-1.49]). The highest wealth-related inequality in bANC (EI: 0.166), at least four antenatal visits (EI: 0.259), FBD (EI: 0.323) and skilled birth attendance (EI: 0.328) (P < 0.05) was observed among women with primary and secondary or higher education. These findings provide strong evidence that there is an interaction effect between education attainment and wealth status in socioeconomic inequalities of maternal health services utilization. Therefore, any approach which will address both women's education and wealth status might be the first step to reducing socioeconomic inequalities in maternal health services utilization in Tanzania.